2022
DOI: 10.3390/jof8101014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biofilm Formation by Candida albicans Strains Isolated from Hemocultures and Their Role in Pathogenesis in the Zebrafish Model

Abstract: Candida albicans, an opportunistic pathogen, has the ability to form biofilms in the host or within medical devices in the body. Biofilms have been associated with disseminated/invasive disease with increased severity of infection by disrupting the host immune response and prolonging antifungal treatment. In this study, the in vivo virulence of three strains with different biofilm formation strengths, that is, non-, weak-, and strong biofilm formers, was evaluated using the zebrafish model. The survival assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…One of the key virulence factors of C. albicans is its ability to form biofilms both on biotic and abiotic surfaces, which can be critical for patients after transplantations [ 37 ]. Here, the biofilm formation assay analysis revealed that C. albicans KS058 has an impaired ability of biofilm formation ( Figure 1 B).…”
Section: Discussionmentioning
confidence: 99%
“…One of the key virulence factors of C. albicans is its ability to form biofilms both on biotic and abiotic surfaces, which can be critical for patients after transplantations [ 37 ]. Here, the biofilm formation assay analysis revealed that C. albicans KS058 has an impaired ability of biofilm formation ( Figure 1 B).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the biofilms' comparisons were made while taking into account C. albicans SC5314 biofilm, which has high hyphae quantity and entanglement [8,11]. The results showed that all of the strains were biofilm formers, regardless of the age group.…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations were carefully chosen, taking into account several previous studies conducted by our group with the same conditions (antifungal drugs used to treat matured biofilms of Candida spp.) [10][11][12][13][14][15].…”
Section: Effect Of Antifungals Against Biofilm Formation Of Different...mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been successfully used for investigating immune responses to both yeast and mould systemic infections (204). In a recent study, C. albicans isolates, with a high or low propensity to form biofilms, were injected in zebrafish larvae to assess in vivo virulence (205). Although fish survival after strong biofilm‐former isolates was significantly reduced, fungal burden was similar after tissue recovery.…”
Section: Innovative and Accessible Animal Models For The Study Of Can...mentioning
confidence: 99%